2018
DOI: 10.1111/jce.13402
|View full text |Cite
|
Sign up to set email alerts
|

Ice or fire? Comparison of second‐generation cryoballoon ablation and radiofrequency ablation in patients with symptomatic persistent atrial fibrillation and an enlarged left atrium

Abstract: Arrhythmia recurrence rates in the two groups during midterm follow-up were comparable. RL creation during CB-Adv ablation resulted in acceptable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Finally, we want to point out that we analyzed only patients undergoing PVI alone in this trial. Some of these patients have been previously reported (60 patients with relatively small left atria and “early persistent” AF as well as 63 patients—all of them with a LA area more than 20 cm 2 , considered to be enlarged—undergoing CB‐PVI compared with RF‐PVI) . Although PVI with CB‐Adv is effective and leads to both PVI and LA substrate modification, the use of CB‐Adv might be insufficient in patients with an enlarged left atrium due to larger residual substrate areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we want to point out that we analyzed only patients undergoing PVI alone in this trial. Some of these patients have been previously reported (60 patients with relatively small left atria and “early persistent” AF as well as 63 patients—all of them with a LA area more than 20 cm 2 , considered to be enlarged—undergoing CB‐PVI compared with RF‐PVI) . Although PVI with CB‐Adv is effective and leads to both PVI and LA substrate modification, the use of CB‐Adv might be insufficient in patients with an enlarged left atrium due to larger residual substrate areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although PVI with CB‐Adv is effective and leads to both PVI and LA substrate modification, the use of CB‐Adv might be insufficient in patients with an enlarged left atrium due to larger residual substrate areas. Possibly an additional LA roof ablation using CB‐Adv as described before may lead to better outcomes as PVI alone, especially in patients with enlarged left atria . Nevertheless, there are no randomized data comparing PVI alone with PVI and additional LA roof ablation in patients with persistent AF using the CB technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CBA, most studies used a second -generation cryoballoon as an ablation tool, except the study by Boveda et al, 8 which utilized a first -generation cryoballoon. For RFA, a contact force -sensing catheter was employed in 3 studies, 9,12,13 while the remaining studies utilized a standard open irrigated catheter. 10,11 Cryo -PVI in 2 CBA groups was reported with no touch -up RFA.…”
Section: What's New?mentioning
confidence: 99%
“…A multicenter retrospective nonrandomized study revealed that CBG2 coupled with RFCA had a 76.6% success rate at 12 months compared to 60.4% for RFCA alone in PaAF and PeAF patients [38]. In the following years, several studies further demonstrated the advantages of a combination of CBG and RFCA [39,40].…”
Section: Longer Time Is Futile To Recurrencementioning
confidence: 99%